Serious creativity and smart applications in the educational process - Obada, Ameer Hadi (Journal of Curriculum and Teaching Methodology, 2025)
The current research aims to conduct a study of the theoretical and practical elements of smart applications, along with serious creativity in the educational process, in order to achieve educational goals and improve the classroom environment for learning. In this study, smart educational applications designed to improve learning motivation and enhance individual learning were examined. The researcher used the theoretical analytical research method to answer the following questions: What is the importance of smart applications in education? What are the requirements for using smart applications in education? What is the importance of serious creativity in the educational process? What are the sources of serious creativity in the educational process? What are the skills that can be taught in serious creativity? Within the presented ideas and theories and based on previous literature and studies, The researcher recommended the necessity of providing professional development for teachers to highlight the educational value of smart applications and innovative thinking strategies.